PROCESO PARA EL CAMBIO DE MEDIDORES MONOFASICOS A BIFASICOS - Estrada Moran, Bruno Xavier (2017)
This project of Reinforcement of the National Distribution System and with the commitment to improve the quality of the electric service in the CORPORACIÓN NACIONAL DE ELECTRICIDAD REGIONAL LOS RÍOS, have been giving significant changes reason why it is necessary to make changes in electrical networks and biphasic meters to improve the quality of service to the user. (Ministry of Energy, 2014). Ecuador proposed to change its energy matrix, part of the change is that we all start cooking based on energy; for this reason the electricity service coverage already exceeds 96% of the national territory and continues to increase. These significant advances in the electrical system and in order to improve the quality of the CNEL EP electric service at National level, The Efficient Cooking Program, this involves the acquisition of Induction Cookers. In view of the demand in has developed a plan of improvement in the medium and low voltage networks with the purpose of performing the CHANGE OF MONOPHASE TO BIPHASIC METERS in the Province of Los Ríos, beginning to execute this plan in Canton Baba and to continue advancing with the rest of cantons that the Province has. The objective is to satisfy all the needs of purchasing growth of citizens, without this entailing at an additional cost to have a meter of greater capacity is avoided internal overload, it is important to emphasize that it is not necessary to change the internal electrical installations, since the appliances will continue to operate without any inconvenience.